Perancangan Sistem Informasi Penjualan E-Commerce Rempeyek Ilhamum-Taza Berbasis Web - Heriyani; Tuty Ulina Malau (Journal of Applied Accounting And Business, 2022)
Ilhamum-Taza is a micro, small and medium enterprise (UMKM) which is engaged in the production and sale of tempe chips and peanut brittle which have become souvenirs from Jambi. UMKM manage the sale of goods is still manual so that the sale of goods is not optimal. Sales management to be more optimal so that it must use a web based e-commerce information system. The development of this web based e-commerce information system uses the waterfall model and the data flow model uses DFD (Data Flow Diagrams) . This research and design produces an e-commerce information system that will be implemented in UMKM Ilhamum-Taza.